Urban Seismic Networks, Structural Health and Cultural Heritage Monitoring: The National Earthquakes Observatory (INGV, Italy) Experience - D'Alessandro, Antonino; Costanzo, Antonio; Ladina, Chiara; Buongiorno, Fabrizia; Cattaneo, Marco; Falcone, Sergio; La Piana, Carmelo; Marzorati, Simone; Scudero, Salvatore; Vitale, Giovanni; Stramondo, Salvatore; Doglioni, Carlo (Frontiers in Built Environment, 2019)
An effective reduction of seismic risk can implement through a multiscale approach to the earthquakes monitoring. Devoted monitoring network are essential to cope with the seismic emergency in urban areas, to assess the damage scenarios, which are useful for the preservation of the strategic functions and services and to improve the community resilience to earthquakes. The National Earthquake Observatory, Italian Institute for Geophysics and Volcanology (ONT-INGV, Italy), has been recently involved in several projects devoted to the reduction of seismic risk by means of the implementation of urban-scale and building-scale monitoring networks. Such systems represent a necessary support for the well-established national seismic network. All these approaches (country, urban, and building scale) could be framed within of a unique system in which each part holds different tasks, with the common final objective of the earthquake risk reduction. In this papers different approaches, experiences and potential capabilities on urban seismic networks, structural health and cultural heritage monitoring implemented in Italy by the ONT-INGV will be presented, with the ultimate goal of achieving an effective integrated multi-scale system.